A Novel Covert Channel for IEEE 802.11 Networks Utilizing MAC Address Randomization - Geovani Teca; Marek Natkaniec (Applied Sciences, 2023)
Vendors implement the MAC address randomization technique to prevent IEEE 802.11 client station devices from being tracked. Although it conceals device identity, it cannot hide its occurring data transmission. This paper presents a novel covert channel that leverages the MAC address randomization technique to create a covert channel to hide data transmission inside IEEE 802.11 networks. The secret data are a disposable random MAC address generated by the IEEE 802.11 station as part of the probe request frame while scanning the network. The paper presents the concept of the covert channel, its implementation, and performance metrics. The study covers diverse scenarios, including the adaptation of the modified Selective Repeat ARQ protocol to alleviate the impact of the number of client stations and their offered loads on the covert channel. The results show that with the appropriate parameter selections, we can adapt the covert channel to produce excellent throughput, efficiency, delay, and jitter according to the environment in which it is installed.